Epithelial-microbial diplomacy: escalating border tensions drive inflammation in inflammatory bowel disease - King, Stephanie J (Intest Res, 2019)
Inflammatory bowel diseases (IBD) are chronic conditions of the gastrointestinal tract-the main site of host-microbial interaction in the body. Development of IBD is not due to a single event but rather is a multifactorial process where a patient’s genetic background, behavioral habits, and environmental exposures contribute to disease pathogenesis. IBD patients exhibit alterations to gut bacterial populations “dysbiosis” due to the inflammatory microenvironment, however whether this alteration of the gut microbiota precedes inflammation has not been confirmed. Emerging evidence has highlighted the important role of gut microbes in developing measured immune responses and modulating other host responses such as metabolism. Much of the work on the gut microbiota has been correlative and there is an increasing need to understand the intimate relationship between host and microbe. In this review, we highlight how commensal and pathogenic bacteria interact with host intestinal epithelial cells and explore how altered microenvironments impact these connections.